VENTAJAS DEL PROCESO DE REFORESTACIÓN SOBRE LA ATENUACIÓN DE LA EROSIÓN Y PROPUESTA DE PROTECCIÓN Y DESARROLLO DE UN ÁREA DE RECARGA EN EL VALLE CENTRAL DE COSTA RICA. - Vargas Sanabria, Asdrúbal (2011)
The results of the study demostrate the reduction of erosion and run-off events in forested areascompared to zones of agricultural use (grassland) in the subbasins of the River Durazno and the upper part of theRiver Virilla, which are considered recharge areas of the deep aquifers for the Central Valley of Costa Rica.Four areas of environmental protection are proposed in this study: 1) the protection of riparian zone, 2) the protection of springs, 3) the planing of agricultural use and 4) the development of comercial forestation.